Methods of a Détoxification Cure, Especially for the Liver - Manfred, Doepp (European Journal of Applied Sciences, 2025)
Modern medicine is increasingly learning how to treat serious diseases. The breadth of the therapeutic spectrum is enormous since biologics, antibodies and AI-generated active substances have become more widespread. Unfortunately, this does not change the fact that there are hardly any truly healthy people left. The frequency of seemingly untreatable chronic complaints is increasing. (1) This could be due to the fact that the body’s environment is deteriorating as a result of toxins of all kinds and an increasingly unnatural diet. It therefore makes sense to review and improve lifestyle, preferably by means of a detoxification cure. This primarily involves strengthening the liver.